Aspects of gender mainstreaming of family and work in Austria - Isabella Buber-Ennser (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
OECD regularly carries out surveys in its member states to assess their recent economicperformance. For the preparation of the 2015 survey focusing on gender mainstreaming of family and work arrangements in challenging times, an OECD team conducted a "factfinding mission" at the Federal Chancellery in Vienna. The mission team approached several researchers and policy makers in order to discuss the recent situation in Austria. The team circulated a strategy note, including a detailed outline of the planned survey, aiming at stimulating scientific and policy-relevant exchanges. In order to discuss the outline of the mission document concerning fertility, migration and the triangular interaction between labour market participation, well-being and parenthood/fertility, I summarized insights from empirical research for Austria based a review of the existing literature. This summary was provided to the OECD team and constituted the major input for discussion.
Keywords: 300; Gender policies; gender mainstreaming; Austria; OECD